Digital technology and changing roles in managerial and financial accounting : theoretical knowledge and practical application - Hamden, Allam; Alareeni, Bahaaeddin; Khamis, Reem (Studies in managerial and financial accounting., 2024)
In today's rapidly evolving digital landscape, technology has permeated every aspect of our lives, revolutionizing the way we communicate, work, and interact with the world around us. The field of accounting is no exception to this digital transformation, as new technologies continue to reshape the roles and responsibilities of professionals in both managerial and financial accounting. Digital Technology and Changing Roles in Managerial and Financial Accounting explores the profound impact of digital technology on the accounting profession. Each chapter provides a deep dive into specific aspects of digital technology and its impact on managerial and financial accounting. We examine case studies, real-world examples, and empirical research to illustrate the practical implications of these technological advancements with the hope that this book inspires readers to embrace the opportunities brought about by digital technology and equips them with the knowledge and insights needed to navigate this evolving landscape.